Primary hyperfibrinolysis as the presenting sign of prostate cancer – A case report - Kulić, Andrijana Djordjije; Cvetković, Zorica; Libek, Vesna (Vojnosanitetski pregled, 2017)
Introduction. A bleeding syndrome in the setting of primary hyperfibrinolysis in a prostate cancer patient is only 0.40–1.65% of cases. The laboratory diagnosis of primary hyperfibrinolysis is based on the increase of biomarkers like D-dimer, fibrinogen split products, plasminogen, and euglobulin lysis test. These tests are not specific for primary hyperfibrinolysis. We reported a rare case of hemorrhagic syndrome caused by primary hyperfibrinolysis as the first clinical symptom of metastatic prostate cancer. Case report. A 64-year-old male was admitted to our hospital with large hematomas in the right pectoral and axillary areas (20 ´ 7 cm), right hemiabdomen (30 ´ 30 cm) and the left lumbal area, (25 ´ 5 cm). The patient had no subjective symptoms nor used any medication. Initial coagulation testing, prothrombin time (PT), and activated partial thromboplastin time (APTT) were within the normal range, while fibrinogen level was extremely low (1.068 g/L) (normal range 2.0–5.0) and the D-dimer assay result was high 1.122 mg/L (normal range < 0.23). The results obtained by rotation thrombelastometry pointed to primary fibrinolysis. Further clinical and laboratory examination indicated progressive malignant prostate disease. First line treatment for the patient was a combined administration of tranexamic acid (3 ´ 500 mg iv) and transfusion of ten units of cryoprecipitate (400 mL). Next day, fibrinolytic function measurements by rotation thrombelastometry were within the normal ranges. Fibrinogen level was normalized within two days (2.4 g/L). There were no newly developed hematomas. Conclusion. This case report shows primary hyperfibrinolysis with bleeding symptoms, which is an uncommon paraneoplastic phenomenon within expanded prostate malignancy. Rotation thrombelastometry in this severe complication helped to achieve the prompt and proper diagnosis and treatment.
Keywords: prostatic neoplasms; blood coagulation disorders; fibrinolysis; hemorrhage; diagnosis; thrombelastography; treatment outcome